여성 주체와 온라인 민족주의 : 〈조선구마사〉 방송 중단 운동을 중심으로 - 신정원(Jeongwon Shin); 오예주(Yezoo Oh); 홍석경(Seok-Kyeong Hong) (언론정보연구, 2022)
2021년 3월 SBS 드라마 <조선구마사>는 역사 왜곡에 대한 시청자들의 비판으로 2회만에 조기 종영했다. 이처럼 빠르게 방송이 중도에 종영된 것은 온라인 커뮤니티를 중 심으로 방송 중단 운동이 거세게 일어났기 때문이다. 네티즌들은 단순한 시청 거부를 넘어 광고사, 제작지원사, 협찬사를 대상으로 불매운동을 벌였다. 본 연구는 <조선구마사> 방송 중단 운동을 온라인 민족주의 운동이라고 보고, 그 주체와 운동 방식에 초점을 맞추어 분석했다. 운동을 주도한 것은 청년 여성 네티즌들로, 더쿠, 여성시대 같은 여초 커뮤니티가 핵심적 역할을 했다. 이들은 정치적 소비자운동과 케이팝 팬덤 문화 를 결합한 운동 방식을 활용하여 방송 중단이라는 목표를 효과적으로 이룰 수 있었다. 기존 연구는 온라인 민족주의의 주체를 (보수) 청년 남성이라고 상정하였으나 <조선 구마사> 방송 중단 운동에서는 청년 여성 네티즌이 온라인 민족주의의 새로운 주체로 활동했다. 그러나 이는 여성 네티즌들이 반중 정서와 조선족 혐오로부터 자유롭지 않 음을 시사한다. 또한 정치적 소비자운동과 케이팝 팬덤 문화가 결합한 운동 방식은 여성 주체의 연대 및 힘돋우기에 기여할 수 있지만, 자칫 대중 문화 검열로 진화할 위험이 있다. In March 2021, the SBS drama <Chosun Exorcist> was canceled after only two episodes due to public criticism about its distortion of history. Its unexpected cancellation was rushed by a fierce boycott in online communities. Netizens did not simply stop watching the program but proceeded to boycott its advertisers and sponsors. This study considers the boycott against <Chosun Exorcist> as an online nationalism movement and analyses its subject and strategy. We suggest that young female netizens led the movement in women’s online communities such as Theqoo and Yeoseongsidae. The movement could be successful by combining political consumerism and K-pop fandom culture. While previous research has implicitly assumed that the subject of online nationalism is (conservative) young men, in the <Chosun Exorcist> cancellation movement, young women netizens acted as a new subject of online nationalism. However, this also implies that young women netizens are not free from anti-Chinese sentiment and hatred towards Chosun-jok. Whereas the unique combination of political consumerism and K-pop fandom culture can contribute to women’s solidarity and empowerment, it also has the risk that it can develop into popular culture censorship. KCI Citation Count: 0